GENIUS LOCI SEBAGAI MODAL ARSITEKTUR BANGUNAN KANTOR POS JAKARTA TAMAN FATAHILLAH DI KAWASAN KOTA LAMA JAKARTA - Sudarmawan Juwono; Heru Wibowo; Karto Wijaya; Abdullah Ali; Keti Andayani; R.Siti Rukayah (Jurnal Arsitektur ARCADE, 2026)
Abstract. The Jakarta Post Office Building at Fatahillah Square is a living monument situated within the historic core of the Jakarta Old Town Heritage Area. Although the building has undergone revitalization, it continues to retain its original function, thereby supporting the development of educational and recreational activities based on heritage conservation, which constitute an important component of Jakarta's urban tourism. Architectural conservation is closely associated with architectural capital, which embodies the significant values and identity of both the building and its surrounding urban context. The genius loci, encompassing both the building's tangible physical attributes and the intangible qualities that shape its identity and uniqueness, constitutes an essential component of this architectural capital and therefore warrants careful consideration in conservation practices. The concept of genius loci provides a framework for exploring the inherent strengths and distinctive characteristics of architectural capital, enabling the construction of an architectural narrative that reinforces the perception and interpretation of the building. This study employs a qualitative approach in which the researcher serves as the primary instrument for exploration, analysis, and interpretation. The findings identify five dimensions of architectural capital derived from the genius loci: functional continuity, the building's role as a marker of urban development, architectural character, physical position, and visual prominence. These dimensions strengthen the building's capacity to construct and communicate a meaningful architectural narrative. Keywords: genius loci; architectural capital; architectural narrative. Abstrak.Gedung Kantor Pos Jakarta Taman Fatahillah adalah living monument pada pusat Kawasan Kota Lama Jakarta yang telah direvitalisasi namun masih mempertahankan fungsi asalnya. Keberadaannya mendukung pengembangan fungsi rekreasi edukatif berbasis pelestarian kawasan yang menjadi obyek pariwisata kota Jakarta. Pelestarian arsitektur berkaitan erat dengan modal arsitektur yang menjadi kekuatan nilai-nilai penting bangunan dan kawasan. Nilai-nilai genius loci pada aspek fisik bangunan dan unsur non fisik yang membentuk eksistensi dan keunikan sebagai modal arsitektur perlu menjadi perhatian dalam pelestariannya. Genius loci menjadi jalan dalam menelusur kekuatan dan karakter modal arsitektur sehingga menjadi narasi untuk memperkuat persepsi arsitektur. Penelitian ini menggunakan pendekatan kualitatif yang menempatkan pengamat sebagai instumen utama dalam melakukan eksplorasi, analisis dan pemaknaan. Temuan modal arsitektur dari aspek genius loci yang didapatkan adalah kontinuitas fungsi, penanda perkembangan kota, karakter arsitektur, posisi fisik dan posisi visual sebagai modal arsitektur bangunan yang dapat memperkuat peran bangunan membangun narasi arsitektur . Kata kunci : genius loci, modal arsitektur, narasi arsitektur